Development of a clothes folding machine / Nur Aliesya Mohamad Saifol and Mohd Fadzli Ismail - Mohamad Saifol, Nur Aliesya; Ismail, Mohd Fadzli (School of Mechanical Engineering, 2023)
The development of a clothes folding machine aims to shorten the time-consuming and demanding task of folding clothes. As folding clothes can be a tedious chore, the machine is designed to reduce the effort and time required to complete the task. The machine will be a semi-automatic system that uses a combination of mechanical and electrical control systems. It was be designed to cater to the needs of the public, particularly housewives, by replicating the manual method of folding clothes. The machine's mechanism started with folding the sleeves, followed by folding the bottom of the shirt, and flipping the shirt to its upper face. The machine was powered by the servo motors and controlled by the Arduino. The machine is expected to revolutionize the clothing industry by providing a convenient and cost-effective way to fold clothes, saving valuable time and energy. The development of the clothes folding machine has the potential to make a significant impact on people's daily lives and is a step towards advancing technological solutions for everyday problems.